The Diagnostic and Prognostic Potential of the B-Cell Repertoire in Membranous Nephropathy - Su, Zuhui; Jin, Yabin; Zhang, Yu; Guan, Zhanwen; Li, Huishi; Chen, Xiangping; Xie, Chao; Zhang, Chuling; Liu, Xiaofen; Li, Peixian; Ye, Peiyi; Zhang, Lifang; et al. (Frontiers in Immunology, 2021)
Membranous nephropathy (MN), an autoimmune glomerular disease, is one of the most common causes of nephrotic syndrome in adults. In current clinical practice, the diagnosis is dependent on renal tissue biopsy. A new method for diagnosis and prognosis surveillance is urgently needed for patients. In the present study, we recruited 66 MN patients before any treatment and 11 healthy control (HC), analysed multiple aspects of the immunoglobulin heavy chain (IGH) repertoire of these samples using high-throughput sequencing. We found that the abnormalities of CDR-H3 length, hydrophobicity, somatic hypermutation (SHM), and germ line index were progressively more prominent in patients with MN and the frequency of IGHV3-66 in post-therapy patients was significant lower than that in pre-therapy patients. Moreover, we found that the IGHV3-38 gene was significantly related to PLA2R, which is the most commonly used biomarker. The most important discovery was that several IGHV, IGHD transcripts, CDR-H3 length and SHM rate in pre-therapy patients had potential to predict the therapeutic effect. Our study further demonstrated that IGH repertoire could be a potential biomarker for prognosis prediction of MN. The landscape of circulating B-lymphocyte repertoires sheds new light on the detection and surveillance of MN.